Violência, punitivismo e criminalização da pobreza : as raízes do estado penal à brasileira - Arend, Kathiana Pfluck (2020)
This dissertation proposes to discuss the roots of punitivism and the Brazilian penal state. The current situation consolidates countless changes present for decades in Brazil, takes on particular nuances with expressions of facist traces of political culture and common sense, which are institutionalized and reverberate in a rhetoric based on hatred. In such a situation, the upsurge of punitivism shapes the need to correct behavior and domesticate bodies. Punitivism is intrinsic to the criminalization of poverty and the increase in barbarism. In this sense, we sought to: analyze how neoliberal punitivism is corroborated by ideological discourses that criminalize poverty, with a view to contributing to its unveiling and to the development of public policies that protect rights for the vulnerable criminal population; to analyze how the criminalization of poverty in the era of neoliberal punitivism has been characterized, in relation to the periods of coup and post-coup; analyze ideological discourses and their economic, political, social and cultural determinants, as well as their repercussions on the criminalization of poverty; problematize the repercussions of ideological discourses of criminalizing poverty; and to identify possible repercussions of the ideological discourses that criminalize poverty in the perception of the punitivism of the representatives of the organs of justice and public security. The analysis is based on Marx's dialectical-critical method and the study is qualitative and exploratory. The categories of the method used were: contradiction, historicity, totality and mediation. The categories are complementary to each other and offer the possibility of a total analysis of the real, observing all aspects that are intrinsic to it. The form of investigation was field research. The research universe was composed of representatives of the justice and public security systems that exercise functions related to social control. The sample consisted of 8 participants. The second source of research was online media, through documentary research, from which forty-five news, opinion articles and reports from the following platforms were selected: El País, G1, HRW and CFCA. The procedures for analyzing the empirical and documentary research were based on the Discursive Textual Analysis. The theoretical categories defined a priori were: ideology, criminalization of poverty, punitivism and neoliberalism. The categories that emerged from the analyzes were: media criminology, punitive moralization, neoliberal rationality, dehumanization / reification and criminal subjection. Considering that the analysis of the current situation needs to be guided by the history of Brazil, the present dissertation makes a historical incursion in analyzing the main governments since the fall of the monarchy. The analysis of the collected information allowed us to understand that the penal State is the fruit and reason for the socio-historical formation of a punitive society, which calls for authoritarianism in the face of crises. Under such prism, political and class conciliation is a product of history and, therefore, punitivism is a form of State action, through structural violence, socially and ideologically accepted, being part and expression of Brazil's socio-historical formation. It is concluded that the responses to violence in the neoliberal punitive era, especially in the context of post-coup 2016, are corroborated by theses hinged on fascist rhetoric, based on hate speech that invariably lead to the upsurge of the penal state.